Studies of Students’ Health in Thailand 4.0 Age According to Principle of Buavana 4 at Mahachulalongkron University - Worachintanaluck , Rinyarat; Phuttaradhammakun, Phrakru; Chaisuk, Peravat (The Journal of Development Administration Research, 2020)
For this thesis, there were three objectives; 1) to study the health of Students in Thailand 4.0 Era according with Principle of Bhavana 4 Mahachulalongkronrajavidyalaya University, 2) to study it according to the principle of growth up (Bhavana 4) of students in Mahachulalongkronrajavidyalaya University, 3) to present it in overview by using the mixed method research with the quantitative and qualitative styles. Consequently, the tools of research doing were the questionnaires for inquiry from the students’ sampling in Mahachulalongkronrajavidyalaya University where they are 247 persons and interview of some administration, masters and officers who are 5 key persons there. Then formation of analysis was the means, standard deviation and contents. Its findings were found that: (1) the well-being of the Thailand 4.0 era of physical health students. Have a healthy body Mental health Have a happy heart Social well being Have good coexistence Cognitive health There were 4 positive aspects of happiness arising from high-mindedness, students had a very good level of knowledge and understanding in health care according to the Thailand 4.0 era (2) Of students Overall, students had opinions on the health conditions of the Thailand 4.0 era according to 4 prayer principles, namely physical prayer, intellectual prayer, spiritual prayer, and spiritual prayer, and (3) health prayer proposal in Thailand 4.0 according to Principles of prayer 4 of students in physical prayer, living a happy life, in the discipline, the prayer, the development of the spiritual precepts, the enhancement of knowledge, thinking and understanding Wisdom prayers to solve problems and have the correct opinion in the truthgrowth was meant that they could learn all time for their life, and finally the intellectual growth was meant that they could solve the problems and stay on the right view according the law of truth.